Systaria barkudensis (Gravely, 1931) is a junior synonym of Palicanus caudatus Thorell, 1897 (Araneae: Miturgidae, Systariinae) - Sankaran, Pradeep M.; Sebastian, Pothalil A. (Zootaxa, 2019)
Thorell (1897) erected the monotypic genus Palicanus based on a single male specimen from Yangon (formerly Rangoon) in Myanmar (formerly Burma). Initially the genus was placed in Drassidae Sundevall, 1833, which later became a junior synonym of Gnaphosidae Pocock, 1898. The genus was subsequently transferred to Clubionidae Wagner, 1887 (Simon 1897) and finally to Miturgidae Simon, 1886 (Lehtinen 1967). Palicanus caudatus Thorell, 1897 is notable because of its mouse-grey appearance (Deeleman-Reinhold 2001) and is currently known to occur in China, Indonesia, Myanmar, Reunion Island and Seychelles (World Spider Catalog 2019). Gravely (1931) described Systaria barkudensis (Gravely, 1931), originally placed under Syrisca Simon, 1886, on the basis of specimens collected from the Indian state of Odisha. The species was redescribed once (Majumder & Tikader 1991) and later it was transferred to Systaria Simon, 1897 (Deeleman-Reinhold 2001). In this paper, we synonymise S. barkudensis with P. caudatus and provide supplementary information on the somatic morphology and male genitalia with detailed illustrations.